2022
DOI: 10.1186/s12879-022-07226-4
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites in stool testing among refugees at a primary care clinic in Toronto, Canada

Abstract: Background Enteric parasites are endemic in many of the countries from which refugees originate. Clinical guidelines vary in approaches to screening for and treating intestinal parasites in refugee receiving countries. This study aims to investigate the prevalence and species of intestinal parasites identified in stool ova and parasite (O&P) specimens in a sample of newly arrived refugees in Toronto, Canada. Methods We conducted a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Among protozoa, E. coli (25.3%), E. nana (14.9%), and G. duodenalis (8.0%) showed a higher prevalence than in other studies [7,30].…”
Section: Discussionmentioning
confidence: 53%
“…Among protozoa, E. coli (25.3%), E. nana (14.9%), and G. duodenalis (8.0%) showed a higher prevalence than in other studies [7,30].…”
Section: Discussionmentioning
confidence: 53%
“…According to Ceccarelli et al [8], the decreased rates of parasitic infections among refugees may be the effect of mass de-worming campaigns conducted under the auspices of World Health Organization and the improvement in sanitation in most developing countries over the last few decades. A study of over 1000 refugees carried out between 2011 and 2016 in Canada demonstrated that although the rate of parasitic infections in the study group reached 40%, most of the infestations were clinically insignificant [9]. All the identified infections were found to have been caused by Blastocystis spp.…”
Section: Discussionmentioning
confidence: 97%